2023
DOI: 10.1096/fj.202202157rr
|View full text |Cite
|
Sign up to set email alerts
|

Iron inhibits glioblastoma cell migration and polarization

Ganesh Shenoy,
Sina Kheirabadi,
Zaman Ataie
et al.

Abstract: Glioblastoma is one of the deadliest malignancies facing modern oncology today. The ability of glioblastoma cells to diffusely spread into neighboring healthy brain makes complete surgical resection nearly impossible and contributes to the recurrent disease faced by most patients. Although research into the impact of iron on glioblastoma has addressed proliferation, there has been little investigation into how cellular iron impacts the ability of glioblastoma cells to migrate—a key question, especially in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…While that study did not examine associations between iron content and survival, it did report that toe nail iron appeared to decrease the further it was collected from the date of glioblastoma diagnosis, suggesting that glioblastoma pathology and iron biology may be more closely associated than previously appreciated 52 . Recent work has also demonstrated novel anti-tumor properties of iron including promoting ferroptosis 22 , inhibiting glioblastoma cell migration 23 , and promoting anti-tumor immunity 24 . In addition to differences in the underlying etiology of anemia, the sexual dimorphism observed in trends between iron supplements and survival may, in part, be explained by differences in iron uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While that study did not examine associations between iron content and survival, it did report that toe nail iron appeared to decrease the further it was collected from the date of glioblastoma diagnosis, suggesting that glioblastoma pathology and iron biology may be more closely associated than previously appreciated 52 . Recent work has also demonstrated novel anti-tumor properties of iron including promoting ferroptosis 22 , inhibiting glioblastoma cell migration 23 , and promoting anti-tumor immunity 24 . In addition to differences in the underlying etiology of anemia, the sexual dimorphism observed in trends between iron supplements and survival may, in part, be explained by differences in iron uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic profiling has also suggested that profiles supporting iron acquisition may be associated with more aggressive phenotypes 21 . Nonetheless, recent work has also highlighted novel aspects of iron biology that may support an anti-tumor role including the promotion of cancer cell ferroptosis 22 , inhibition of glioblastoma cell migration 23 , and promotion of anti-tumor immunity 24 .…”
Section: Introductionmentioning
confidence: 99%